2016
DOI: 10.1016/j.bpj.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

MreB Orientation Correlates with Cell Diameter in Escherichia coli

Abstract: Bacteria have remarkably robust cell shape control mechanisms. For example, cell diameter only varies by a few percent across a given population. The bacterial actin homolog, MreB, is necessary for establishment and maintenance of rod shape although the detailed properties of MreB that are important for shape control remained unknown. In this study, we perturb MreB in two ways: by treating cells with the polymerization-inhibiting drug A22 and by creating point mutants in mreB. These perturbations modify the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(138 citation statements)
references
References 39 publications
8
127
0
Order By: Relevance
“…In all cases, the cells producing mCherry‐tagged MreB were slightly thicker than the corresponding untagged MreB producing cells. This is consistent with the previous reports that cells producing fluorescent protein‐tagged MreB are slightly thicker than cells producing untagged MreB (Billaudeau et al, ; Ouzounov et al, ). However, the general tendency was that cells producing MreB A174T were thicker and cells producing MreB A125V were thinner than WT cells.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In all cases, the cells producing mCherry‐tagged MreB were slightly thicker than the corresponding untagged MreB producing cells. This is consistent with the previous reports that cells producing fluorescent protein‐tagged MreB are slightly thicker than cells producing untagged MreB (Billaudeau et al, ; Ouzounov et al, ). However, the general tendency was that cells producing MreB A174T were thicker and cells producing MreB A125V were thinner than WT cells.…”
Section: Resultssupporting
confidence: 93%
“…Growth and morphology of cells producing MreB‐mCherry SW were comparable with those of WT cells (Bendezú et al, ). During this project, it was reported that msfGFP does not affect the function of MreB and thus msfGFP is a better choice than mCherry for fusion with MreB (Ouzounov et al, ). Thus, we re‐evaluated the effect of fusion of MreB with mCherry by analyzing the length, width and sensitivity to A22 of cells producing MreB mutants tagged with mCherry or untagged (Supporting Information Figures S1 and S2, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 MreB monomers polymerize into filaments that rotate circumferentially around the long axis of cells. 101104 E. coli MreB is positioned in contact with the cytoplasmic membrane through an N-terminal amphipathic helix 105 and has been hypothesized to localize a protein complex containing proteins that perform peptidoglycan synthesis and degradation to regions of the cell wall with negative curvature. 106,107 The directed motion of MreB in these regions of the cell is correlated with peptidoglycan assembly and enables cells to maintain a rod shape, 107 as inhibiting MreB function causes cells to gradually change shape from a rod to a sphere.…”
Section: Bacterial Proteins That Hypothetically Contribute To Cell Stmentioning
confidence: 99%
“…However, Γ values are only directly comparable if two particles have the same α. Therefore, to directly compare the speed over short distances of particles with different α, we report τ* as the time it takes a particle to explore a set area (0.5 μm, the typical size of an MreB focus) (16).…”
Section: Significancementioning
confidence: 99%